Application of quantitative computer-based analysis for student’s learning tendency on the efficient utilization of mobile phones during lecture hours - Mortazavi, Mohsen; Tansu, Fatma; Davarpanah, Afshin (MDPI, 2020)
The rapid pace of development and technology enhancements revolutionize the way people communicate and subsequently exert a considerable influence on a student’s involvement and motivation. Mobile phones are considered among the most important devices to have made a breakthrough in every aspect of human life. Students’ persistence in using mobile phones during classroom hours has become a significant concern because of distractions, disruptions, cheating, and inappropriate use. The objective of this paper is to identify the reasons why students use mobile phones during lecture hours by quantitative computer-based analysis. The participants were 520 undergraduate students who completed a questionnaire that is significantly based on the comparison of three principal perceptions of age, gender, and grades. To investigate the reliability of the proposed factors, Cronbach’s alpha parameter was adequately utilized in this study to check the consistency adaptation of these factors and to provide questions on the questionnaire. To validate the measurement scales, qualitative content validity was taken into consideration. The analysis of the correlation matrix that is based on the six administered variables in this study has been conducted in the statistic correlation level of 0.01, which is ranged from 0.043 to 0.601. Although no statistically significant differences were found in the students’ perception regarding their gender and age, the differences were significant regarding their grades as far as the addiction reason was concerned. Consequently, the overwhelming majority of the students tended to use mobile phones during the lecture hours for class-related purposes. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Classroom; Correlation matrix; Cronbach’s alpha parameter; Mobile learning; Undergraduate university students